HOW STRUGGLE PRIMARY PRESERVICE TEACHERS DEFINE ETHNOSCIENCE? - Wibowo, Agus Mukti; Amelia, Rizki; Sugiri, Wiku Aji; Priatmoko, Sigit (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
This research aims to analyze the perspective of Primary Preservice Teachers about Ethnoscience. This study used quantitative research with a survey method. This research was conducted at the Madrasah Ibtidaiyah Teacher Education study program, UIN Maulana Malik Ibrahim Malang. The research sample used 92 primary preservice teachers in third and fifth grade. The instrument of this research is in the form of a questionnaire which is distributed online via a google form. The research instrument was compiled based on the operational definition of ethnoscience. The questionnaire consists of 9 closed questions about the concept of ethnoscience and 1 open question about examples of ethnoscience. The research results show that in quantitative data almost all preservice teachers agree about the connection between science learning and local wisdom. However, the open-ended questionnaire showed that 93,4% of preservice teachers struggle to give an example about ethnoscience. Thus, it is recommended that preservice teachers be equipped with ethnoscience knowledge, so when they become real teachers, they know how to use ethnoscience in the classroom.